Álvares de Azevedo e bipolaridade: uma iluminação recíproca - Oliveira, Carlisson Morais de (2023)
The premise of this thesis is twofold: reading Álvares de Azevedo's poetry, based on bipolarity, helps the perception of his poetry; simultaneously, his poetry — his art with words — helps illuminate the states and feelings of bipolar people. The work is divided into two parts. In the first, the author and his works are discussed; in the second, academic influences and approaches. In particular, we argue that the division of the Lira dos Vinte Anos, into the well-known "First" and "Second", can be read as groupings of poetry mostly, but not exclusively, linked to the two states of bipolarity: "First part", depression; "Second part", mania. We selected some poems that show the poet's awareness, in the circle of bipolarity, which I called "Complete Cycle". Therefore, we propose a reading for the binomial mentioned by Álvares de Azevedo himself in Lira. The first chapter addresses the issue of the author, in literary criticism, based on Barthes and Landy. In the second, his bipolarity is discussed, as he is largely influenced by the work Touched with Fire by Kay Redfield Jamison (1993). It begins with a commentary on bipolarity, based on psychiatry, particularly the DSM-5-TR (2023) and Diogo Lara (2009), detailing bipolarity Type I, Type II and Cyclothymia. The third chapter is composed of analyzes of individually addressed poems, divided into two sections: a) upwards; b) down.